IMPLEMENTASI KOMUNIKASI DALAM PENGENDALIAN TUBERKULOSIS PARU STUDI KASUS: PUSKESMAS SIKO DAN KALUMATA KOTA TERNATE - Muliana Muliana (Poltekkes Kemenkes Jayapura, 2021)
ABSTRACT Tuberculosis (TB) is a direct infectious disease caused by the bacteria Mycobacterium tuberculosis. Based on the 2017 Global Tuberculosis Report, globally new tuberculosis cases amounted to 6.3 million, equivalent to 61% of tuberculosis incidents (10.4 million). Tuberculosis remains the 10 highest cause of death in the world and tuberculosis mortality globally is estimated at 1.3 million patients. The purpose of this study was to determine the Implementation of Communication in the Control of Pulmonary Tuberculosis in the Siko and Kalumata Puskesmas in Ternate City. In this study, researchers used a mix method. The research location is in the working area of the Siko and Kalumata Community Health Centers. The size / number of informants in this study is determined on the basis of saturation theory (the point in managing data when new data no longer brings additional insight to the research question). The informants in this study were the Head of the Community Health Center Head of the Sub-District Head Office, Religious Leaders, Community Leaders, Health Cadres and TB Patients. Communication has an important role in controlling pulmonary tuberculosis, various structured programs from the global WHO level to regional city governments are trying to do this and then duplicated and implemented in the working areas of the Siko and Kalumata Puskesmas. Results of research on the implementation of communication generally show that the category is not good enough as much as 48.0% and quite good 52.0%. There is no difference in the mean value of communication between the two working areas of the Siko and Kalumata puskesmas. In addition, a more innovative communication approach is needed and that touches the community so that they can independently try to participate in controlling pulmonary tuberculosis either by adhering to treatment, or taking part in preventing an increase in new cases. Keywords: Tuberculosis (TB), communication